264-channel high-performance magnetic field detection system for transcranial magnetic stimulation (TMS). (November 2020) - Xiong, Hui; Chen, Kunhan; Liu, Jinzhen; Qi, Hailong; Tian, Kaiwen
Highlights: A novel procedure is proposed to calibrate transcranial magnetic stimulation device. A high performance and low cost multi-channel DAQ card is proposed. Real-time detection and data transmission of TMS pulsed magnetic field. The performance of the system was evaluated and compared. The result of the calibration of real TMS magnetic field. Abstract: To calibrate transcranial magnetic stimulation (TMS) devices before clinical trials, a 264-channel high-performance magnetic field detection system for TMS is proposed in this paper. The magnetic field detection system consists of three parts: 3D magnetic field measurement sensor (MFMS) array, 264-channel data acquisition (DAQ) card and monitor software. The 3D MFMS array is made of induction coils according to the structure of human brain. The DAQ card has 264 channels, with 4 MSps/ch maximum sampling rate and 14-bit resolution, and a good signal noise and distortion (SINAD) and crosstalk of 65.1 dB and −83.4 dB respectively. FPGA is used to control and process high-speed signals in the DAQ card. The monitor software is developed in QtCreator5.12 to process, display and backup data. The system, which is suitable for various TMS devices, can detect TMS magnetic field in real time with a relative error (RE) of 2.19%. Finally, the proposed system is used to calibrate our TMS device. The results show a good match between measurements and simulations of the TMS device with an average RE of 3.72%, which proves the system has outstanding advantages in multi-channel, synchronization, dynamic performance, data throughput, data visualization and so on.